PKM Pemberdayaan Pemandu Lingkungan dan Katekis: Workshop Peran Spiritualitas Katekis dalam Pengembangan Formatio Iman Berjenjang di Paroki Santo Krisologus BSB Semarang - FR. Wuriningsih; Gregorius Daru Wijoyoko (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
Community Service Activities (PKM) carried out at St. Peter Krissologus Parish BSB aims to strengthen the spirituality and pastoral skills of catechists through a principle-based approach of "Life, Joy, and Love." This program is organized by the Catechetical Pastoral College (STPKat) of Saint Francis Assisi, guided by the General Instruction Manual of Catechetes. The multidimensional approach is applied through lectures, interactive discussions, case studies, and group dynamics, which are expected to be able to create catechists who live according to faith, bring the joy of the gospel, and serve with sincere love. The results show that catechists are increasingly motivated and ready to face ministry challenges. The development of aspects of digitization of catechesis and deepening of the liturgy is suggested as a sustainability measure.